Vemurafenib Treatment of Pleomorphic Xanthoastrocytoma in a Child With Down Syndrome - Petruzzellis, Giuseppe; Valentini, Diletta; del Bufalo, Francesca; Ceglie, Giulia; Carai, Andrea; Colafati, Giovanna Stefania; Agolini, Emanuele; Diomedi-Camassei, Francesca; Corsetti, Tiziana; Alessi, Iside; Mastronuzzi, Angela; Locatelli, Franco; et al. (Frontiers in Oncology, 2019)
Brain tumors are the most common solid neoplasms of childhood, but they are very rarely reported in children with Down Syndrome (DS), who develop more commonly different types of malignancies. In particular, we hereby report the case of an 8-year-old child with DS that presented to our attention for neurological and endocrinological issues. Brain imaging revealed the presence of a mass that was partially resected revealing a histological diagnosis of Pleomorphic Xanthoastrocytoma (PXA), a rare brain tumor. These tumors can harbor the BRAF mutation V600E, targetable by the specific inhibitor Vemurafenib. After confirming the presence of the mutation in the tumor, the patient was treated with Vemurafenib. The treatment proved to be effective, leading to a partial response and a stabilization of the disease. Patient with DS usually show a higher toxicity of chemotherapy and often a reduction of the dose of chemotherapeutic drugs id necessary. Vemurafenib was instead well tolerated as the only observed adverse effect was grade I skin toxicity. This is, to our knowledge, the first case of a PXA reported in a child with DS and the first DS patient treated with Vemurafenib.